Correlation between Coenzyme Q10 Level Long-Term Steroid Inhalation in Patients with Bronchial Asthma - Deny Perdana Putra1, Arief Bakhtiar2, Muhammad Amin2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: The main therapy of asthma is inhaled steroids and is often used for long periods of time. Coenzyme Q10 is a potent antioxidant produced largely by mitochondria. Treatment of long-term oral steroids can cause mitochondrial damage which lowers the level of coenzyme Q10. Objective: To analyze the relationship between coenzyme Q10 levels and long-term steroid inhalation in asthma patients. Method: The study was conducted at Asthma Unit/COPD of Dr. Soetomo General Hospital Surabaya Indoensia, Pulmonology Unit of. Dr. M. Soewandhie General Hospital Surabaya Indonesia, and Pulmonology Unit of Universitas Airlangga Hospital Surabaya Indonesia. We measured coenzyme Q10 levels and the duration of inhaled steroid use in the subjects. The data were processed using computer statistics program. The correlation between coenzyme Q10 level and long-term steroid inhalation was analyzed using Pearson correlation test (p <0.05). Result: Coenzyme Q10 levels in all samples were normal and increasing. There was no low coenzyme Q10 level found in all samples. The result of Pearson’s correlation test between coenzyme Q10 level with longterm steroid inhalation showed r = -0.037; p = 0.848 (p> 0.05). Conclusion: There was no correlation between coenzyme Q10 level and long-term steroid inhalation found in this study.